2016
DOI: 10.1080/1828051x.2015.1128691
|View full text |Cite
|
Sign up to set email alerts
|

Effects of abrupt housing changes on the welfare of Piedmontese cows

Abstract: The Italian Piedmontese cattle breed is traditionally housed in tie-stalls and, to a lesser extent, in loose housing systems with free stalls. The present study has compared the same group of 15 cattle before and after stable renovation (tie-stall vs free-stall housing) funded by Regulation (EU) No. 1305/2013. All the animals remained healthy during the trial, no clinical signs were observed and no mastitis occurred. The tested parameters were: locomotion scoring system, salivary cortisol, blood parameters, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 43 publications
0
19
1
Order By: Relevance
“…The comparison between freestall and tiestall housing was less clear: 2 studies found improved locomotion scores in freestalls compared with tiestalls (Kara et al, 2011;Ostojić-Andrić et al, 2011), 3 found neutral effects (Wells et al, 1993;Olechnowicz et al, 2010;Popescu et al, 2014), and 2 found positive effects of tiestall housing (Cook, 2003 andSogstad et al, 2005). After a move from tiestalls to freestalls, Tarantola et al (2016) found no change in lameness. Enriquez-Hidalgo et al (2018) tracked locomotion scores as cattle transitioned from pasture, to tiestalls, and back, and noted that scores worsened after confinement.…”
Section: Lamenessmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparison between freestall and tiestall housing was less clear: 2 studies found improved locomotion scores in freestalls compared with tiestalls (Kara et al, 2011;Ostojić-Andrić et al, 2011), 3 found neutral effects (Wells et al, 1993;Olechnowicz et al, 2010;Popescu et al, 2014), and 2 found positive effects of tiestall housing (Cook, 2003 andSogstad et al, 2005). After a move from tiestalls to freestalls, Tarantola et al (2016) found no change in lameness. Enriquez-Hidalgo et al (2018) tracked locomotion scores as cattle transitioned from pasture, to tiestalls, and back, and noted that scores worsened after confinement.…”
Section: Lamenessmentioning
confidence: 99%
“…Several of the affective states addressed were derived from the WQA protocol including "absence of prolonged hunger" (evaluated by means of BCS; Ostojić-Andrić et al, 2011;Popescu et al, 2013Popescu et al, , 2014, and good "human-animal relationship" (evaluated via avoidance distance; Mattiello et al, 2009;Popescu et al, 2013Popescu et al, , 2014. The theme of "comfort" [expressed as "cow comfort" (Haley et al, 2000), "comfort situation" (Tarantola et al, 2016), and"comfort around resting" (Plesch et al, 2010;Ostojić-Andrić et al, 2011;Popescu et al, 2013Popescu et al, , 2014] was addressed in 6 of the 14 studies. Stress, as measured by physiological parameters such as cortisol, was addressed in 7 studies (Varner et al, 1983;Redbo, 1992Redbo, , 1993Higashiyama et al, 2007;Veissier et al 2008;Tarantola et al, 2016;Peric et al, 2017).…”
Section: Affective Statementioning
confidence: 99%
“…The housing system could play an important role in cattle welfare [7]. Loose housing systems allow more freedom of movement than tether systems, also offering the animals the possibility of experiencing more natural social behaviors.…”
Section: Farm Animals 21 Cattle and Small Ruminantsmentioning
confidence: 99%
“…With regards to tied Piemontese animals, the identification of higher 20b-dihydrocortisol values may suggest a potential effect of the housing system, as previously reported by Starvaggi Cucuzza (2014). Tarantola et al (2016), in the assessment of welfare of cows moving from a tied stall housing system to a free housing system, also observed that salivary cortisol levels were higher before the housing change, thus supporting the hypothesis that a tied stall housing system is a remarkable stress factor in adult cattle.…”
Section: Discussionmentioning
confidence: 54%